2023
DOI: 10.20885/risfe.vol2.iss1.art7
|View full text |Cite
|
Sign up to set email alerts
|

Sharia e-commerce in Indonesia: Sharia peer to peer lending

Abstract: Purpose – This article discusses the increasingly rapid development of the sharia e-commerce in Indonesia, focusing on FinTech peer to peer lending sharia.Methodology – This article uses qualitative methods and literature research (library research), with descriptive analysis techniques related to sharia FinTech lending in Indonesia, as well as a statutory approach, which is classified based on hierarchy and sources of law by comprehensive review.Findings – The theme of this article is that Islamic FinTech len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Moreover, one reason for this could be that the ease of use is not the primary concern for users when it comes to Sharia peer-to-peer lending. Instead, other factors such as trust, religiosity, and perceived usefulness may play a more significant role in determining the likelihood of adoption (Alrasyid et al, 2023;Hanif & Santosa, 2023;Sari et al, 2023). This suggests that users may prioritize other factors over ease of use when evaluating the suitability of a Sharia peer-to-peer lending platform.…”
Section: Figure1 Hypothesis Testing Resultsmentioning
confidence: 99%
“…Moreover, one reason for this could be that the ease of use is not the primary concern for users when it comes to Sharia peer-to-peer lending. Instead, other factors such as trust, religiosity, and perceived usefulness may play a more significant role in determining the likelihood of adoption (Alrasyid et al, 2023;Hanif & Santosa, 2023;Sari et al, 2023). This suggests that users may prioritize other factors over ease of use when evaluating the suitability of a Sharia peer-to-peer lending platform.…”
Section: Figure1 Hypothesis Testing Resultsmentioning
confidence: 99%
“…The contribution of regulatory supervision is one of the causal factors. A survey conducted by Sari (2023) also reported that as many as 83% of Sharia P2P Lending platforms complained about the unclear regulations regarding business models and Sharia financial schemes permitted in P2P Lending.…”
Section: Introductionmentioning
confidence: 99%